Association of working memory and elevated overnight urinary norepinephrine in patients with schizophrenia. (May 2021) - Savransky, Anya; Chiappelli, Joshua; Du, Xiaoming; Carino, Kathleen; Kvarta, Mark; Bruce, Heather; Kochunov, Peter; Goldwaser, Eric; Tan, Yunlong; Hare, Stephanie; Hong, L. Elliot
Abstract: Introduction: Norepinephrine has both central and peripheral origins and is known to influence cognitive processes in attention, learning, and working memory, but the research regarding the impact of norepinephrine on cognition in schizophrenia remains sparse, and mainly focuses on centrally regulated noradrenergic effects. This study examined the relationship between cumulative overnight norepinephrine levels in the urine and working memory in patients with schizophrenia and healthy controls. Methods: Urinary catecholamines were collected overnight in patients with schizophrenia (n = 75) and healthy controls (n = 33). Working memory was assessed using the digit sequencing task. Results: Patients showed significantly higher average levels of overnight norepinephrine (t(103.10) = −3.16, p = 0.002) and reduced working memory performance (t(90) = 3.87, p = 0.001) compared with healthy individuals. There was a significant negative correlation between norepinephrine and working memory in patients (r = −0.38, p = 0.005), but not in controls (r = 0.08, p = 0.67). After controlling for age, sex, antipsychotic medications, and serotonin-norepinephrine reuptake inhibitor-based antidepressants, the correlation remained significant (r = −0.41, p = 0.004). Conclusions: High peripheral overnight levels of urinary norepinephrine are associated with lower working memory performance in patients with schizophrenia. These results parallel previous studies suggesting that high levels of central norepinephrine may result in working memory impairments. As norepinephrine rapidly breaks down and usually does not pass through the blood-brain barrier, the potential effect of peripheral cumulative norepinephrine on working memory is intriguing, and needs to be further investigated.